An update on new low add multifocal intraocular lenses. Issue 4 (July 2016) - Rojas, Mario J.; Yeu, Elizabeth
Abstract : Purpose of review: The purpose of this article is to provide an overview and update on recent literature regarding low-add multifocal intraocular lenses (MFIOLs). Recent findings: Clinical and benchwork studies involving low-add MFIOLs were reviewed. Clinical studies focused on uncorrected distance, intermediate, and near vision, along with secondary dysphotopsias. Studies done in the laboratory assessed the optical properties of various lenses, and optically replicated visual scenarios at different viewing distances. Summary: MFIOLs continue to evolve to meet the needs of an evolving patient population. Low-add MFIOLs have been shown to improve intermediate vision, while not compromising distance vision, along with decreasing dysphotopsias. Their optical properties continue to be optimized, and with these new improvements, larger groups of patients can benefit from the range of vision provided. It is important to understand the strengths and limitations of these new MFIOLs, this review provided the most up to date review of the literature describing low-add MFIOLs. The new information provided by these reviewed articles allows the ophthalmologist to provide the best options for each individual patient.